4D flow evaluation of blood non-Newtonian behavior in left ventricle flow analysis. (15th April 2021) - Riva, Alessandra; Sturla, Francesco; Caimi, Alessandro; Pica, Silvia; Giese, Daniel; Milani, Paolo; Palladini, Giovanni; Lombardi, Massimo; Redaelli, Alberto; Votta, Emiliano
Abstract: Blood is generally modeled as a Newtonian fluid, assuming a standard and constant viscosity; however, this assumption may not hold for the highly pulsatile and recirculating intracavitary flow in the left ventricle (LV), hampering the quantification of fluid dynamic indices of potential clinical relevance. Herein, we investigated the effect of three viscosity models on the patient-specific quantification of LV blood energetics, namely on viscous energy loss ( EL ), from 4D Flow magnetic resonance imaging: I) Newtonian with standard viscosity (3.7 cP), II) Newtonian with subject-specific hematocrit-dependent viscosity, III) non-Newtonian accounting for the effect of hematocrit and shear rate. Analyses were performed on 5 controls and 5 patients with cardiac light-chain amyloidosis. In Model II, viscosity ranged between 3.0 (−19%) and 4.3 cP (+16%), mildly deviating from the standard value. In the non-Newtonian model, this effect was emphasized: viscosity ranged from 3.2 to 6.0 cP, deviating maximally from the standard value in low shear rate (i.e., <100 s −1 ) regions. This effect reflected on EL quantifications: in particular, as compared to Model I, Model III yielded markedly higher EL values (up to +40%) or markedly lower (down to −21%) for subjects with hematocrit higher than 39.5% and lower than 30%, respectively. Accounting for non-Newtonian blood behavior on a patient-specific basis may enhance the accuracy of intracardiac energetics assessment by 4D Flow, which may be explored as non-invasive index to discriminate between healthy and pathologic LV.